2016
DOI: 10.1161/jaha.115.002620
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Monitoring and Arrhythmic Outcomes in Pediatric and Adolescent Patients With Duchenne Muscular Dystrophy

Abstract: BackgroundPatients with Duchenne Muscular Dystrophy (DMD) develop cardiac fibrosis and dilated cardiomyopathy. We described the frequency of significant Holter findings in DMD, the relationship between cardiac function and arrhythmia burden, and the impact of these findings on clinical management.Methods and ResultsA retrospective review was done of patients with DMD who received a Holter from 2010 to 2014. Clinical and arrhythmic outcomes were analyzed. Patients were classified based on left ventricular eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…174,175 However, 2 recent retrospective studies of ambulatory electrocardiographic monitoring by guest on May 9, 2018 http://circ.ahajournals.org/ Downloaded from e210 results in 235 DMD patients 14±4 years of age and 91 patients 17±4 years of age found only LVEF <30% to 35% and increased age (eg, ≥17 years) were associated with abnormal ambulatory electrocardiographic findings, such as nonsustained atrial and ventricular tachycardias. 22,23 Because of limitations in mobility with disease progression, the role of exercise testing in DMD and BMD is somewhat limited. …”
Section: Cardiac Evaluation In Dmd and Bmdmentioning
confidence: 99%
“…174,175 However, 2 recent retrospective studies of ambulatory electrocardiographic monitoring by guest on May 9, 2018 http://circ.ahajournals.org/ Downloaded from e210 results in 235 DMD patients 14±4 years of age and 91 patients 17±4 years of age found only LVEF <30% to 35% and increased age (eg, ≥17 years) were associated with abnormal ambulatory electrocardiographic findings, such as nonsustained atrial and ventricular tachycardias. 22,23 Because of limitations in mobility with disease progression, the role of exercise testing in DMD and BMD is somewhat limited. …”
Section: Cardiac Evaluation In Dmd and Bmdmentioning
confidence: 99%
“…The question remains whether this guidance is appropriate for adult patients with BDMD. There is little evidence to guide ICDs use in paediatric patients generally and virtually none in children with DMD [30,31] . One singlecentre study repored a low risk of rhythm abnormalities in paediatric DMD patients whose LVEF was greater than 35% [26] .…”
Section: Pacemakers And/or Defibrillators In Dmd / Bmdmentioning
confidence: 99%
“…When hypoxaemia / hypercapnia and left ventricular dysfunction interact, the risk of sustained arrhythmias is increased. However, based on the results of ECG-Holter, ECG signal averaging and limited invasive electrophysiology studies in patients with DMD, he concluded that ventricular arrhythmia risk tracks primarily with the severity of left ventricular dysfunction [24,31,65,66] . As such there is little evidence that patients are at risk of sustained atrial or ventricular arrhythmias until cardiomyopathy is advanced.…”
Section: Arrhythmia Risk / Cardiac Electrophysiology In Dmdmentioning
confidence: 99%
“…The ability to effectively deliver a systemic signal that triggers precise postnatal genetic modification has already been applied to mouse models of Duchenne muscular dystrophy using CRISPR/Cas9 and AAV strtategies. 1214 The heart is a particularly attractive target for a proactive approach with this disease as heart disease overtly presents later in life, 15 and indeed with improved respiratory care heart failure is now the most common cause of death in in DMD. 16 To effectively treat the skeletal muscle disease, it will probably be necessary to target the mouse satellite cells or muscle stem cells, which may be more refractory to viral mediated interventions.…”
Section: Postnatal Genome Editingmentioning
confidence: 99%